The patterns of healthy behavior for students to evaluate the curriculum of the department of students’ activities at Southern Technical University - Makttoof, Adnan Alwan; Dakhil, Rabeea Lafta; Oleiwi, Abbas Mohsin (International Journal of Psychosocial Rehabilitation, 2020)
The introduction on healthy behavior and its development includes increasing importance, and understanding the underlying relationship between behavior and health has led to major shifts in understanding and developing health, and the possibility of influencing them at the individual level, and health is no longer a negative concept of what can be achieved in all cases, but rather has become A dynamic concept, needs. An effort by individuals to achieve and maintain it, that the importance of research is necessary to identify the reality of a healthy behavior pattern among students of human and scientific colleges who are participants and not involved in sporting activities in the plan and the mathematical internal curriculum to manage student sporting activities at Thi-Qar University on the impact of participation or not. To promote healthy behavior patterns among college students that food and physical activity have a significant impact in avoiding an individual to gain weight and be exposed to obesity and reduce the risk of developing many chronic diseases such as cardiovascular diseases that are caused by obesity significantly and represent obesity and overweight rates among students. As for the research objectives, they were to identify the patterns of healthy behavior of students, and the human fields were: a sample of students of human and scientific colleges from the colleges of Thi-Qar University (345) students distributed on human and scientific colleges, and the temporal field: for the period from 1/10/2018- until 5/10/2019 and the spatial field: Thi-Qar University’s Humanitarian and Scientific Colleges 2019, and the third chapter covered the use of the descriptive approach by the researchers in the analytical method for its suitability to the aim and nature of its procedures. The sample of the research is among the students of human and scientific colleges who are not participating in student activities. (30) Students as an exploratory sample at a rate of (8.7%) divided into two groups, a group not participating in the activities, and (13) students with a percentage of (33.23%) (17) students with a ratio of 59.56%) of the participants, while the sample on which the scale was applied (315) students with a percentage of (91.3%) as a basic sample divided into two groups, a group of non-participants in student activities, and (135) students with a percentage of (42,86%), while participants (180) with a percentage of (57.18%) of participants in student activities, according to Plan The student activities measure. It was presented and interpreted the results of the responses of the research sample from students not participating in sports activities in the annual curriculum, and presented and interpreted the results of the responses of the research sample from students participating in student activities according to the annual curriculum. As for the research findings, the nutritional behavior of students participating in student activities They were more aware of the percentages of fats, protein and carbohydrates appropriate in their daily food, more careful that their diets contain the five essential elements, and more interested in reducing sweets and fatty pastries eaten. Social behavior: Participants in student activities emphasized that most of them were more in touch with others and had good relations with those around them and wanted to talk about their interests from close and continuous communication. Personal behavior: Students participating in student activities where they were more interested in searching for health information, and are keen to use a toothbrush after eating meals, in addition to their interest in reading books and scientific journals, leisure time behavior: Students participating in student sports activities confirmed that they are interested in exercising physical activity from In order to achieve health and fitness, and that the physical exercises that they exercise in their spare time are walking, running and games. Individuals and groups, and those they have the ability to assess their levels of physical fitness- wrong behavior. Students participating in student activities emphasized their reluctance to drink unhealthy drinks and smoking, with an interest in pulse rates during physical activity and sleep in low light, and to see a doctor. Periodically, there are statistically significant differences between the axes of the questionnaire form (food behavior- social behavior- personal behavior- leisure time behavior), the valid sample of the research sample of students participating in the activities of the general plan of sports activity management in Thi-Qar University in the curriculum of student activities, in light of the results and conclusions, the researcher recommends that Follows: Attention to the promotion of sports culture among students, upon their joining the university, on the need to participate in student activities. Sports so that behavior and health concepts can be modified taking into consideration work on student participation in activities that contribute to strengthening when the results showed that there are statistically significant differences in the wrong behavior axis) good students who are not involved in student activities interest in spreading the rules of wrong practice they have organized for sports activities, which contributes to study materials To make the development of mathematical cognitive awareness a mathematical practice a student curriculum.